A Study Of The Impact Of Six Sigma Deployment On Firm Performance: A Case Study In A Small Scale Palm Oil Mill - Huat, Tee Wee (2009)
The case study is conducted in a small size oil palm mill with the objective to assess practicality of Six Sigma adoption in small and medium size organization. The challenge in Six Sigma today is the adoption of Six Sigma program in the smaller and medium size companies (SME).